PENDUGAAN POTENSI HUTAN SAGU DENGAN MENGGUNAKAN TEKNIK PENGINDERAAN JAUH - Ishak Sumantri Haryono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
The aim of this study is to apply remote sensing techniques to estimate sago potential. The estimation method of sago potential is a linear regression equation. Estimate parameter from aerial photo scale of 1: 20000 is the crown density as dependent variable while sago soft core (empulur) volume as the in dependent variable. . The linear regression equation of the sago potential is Ŷ = 3.6731 X + 147.43 with 0. 7313 coefficient corelation. Based on the study the linear regression equation above appear to have reliable estimate and proved to be useful for planning of sago forest management.